Predictive factors for survival of oligometastatic colorectal cancer treated with Stereotactic body radiation therapy. (April 2019) - Franzese, Ciro; Comito, Tiziana; Toska, Eno; Tozzi, Angelo; Clerici, Elena; De Rose, Fiorenza; Franceschini, Davide; Navarria, Pierina; Reggiori, Giacomo; Tomatis, Stefano; Scorsetti, Marta
Highlights: Increasing time from diagnosis of metastases to Stereotactic body radiation therapy is negatively impacting on local control. In-field progression and increasing number of systemic lines are significant negative predictive factors for progression free survival in oligometastatic colorectal cancer. Median overall survival of patients with ablated metastases is 1.6 fold longer than patients without control of oligometastases. Abstract: Background and purpose: Colorectal cancer (CRC) represents one of the major leading causes of death from cancer. Aim of the present study was to analyze outcome of oligometastatic CRC patients treated with stereotactic body radiation therapy (SBRT), and to evaluate predictive factors of survival. Materials and methods: We included patients with maximum 5 metastases. Previous/concomitant systemic treatments were allowed. End points of the present study were the outcome in terms of Local control of treated metastases (LC), progression free survival (PFS), and overall survival (OS). Results: 437 metastases were treated in 270 patients. Lung was site of metastases in 48.5% of cases, followed by liver (36.4%). Systemic treatment was administered before SBRT in 199 patients (73.7%). Median follow-up time was 23 months (3–98.7). Rates of LC at 1, 3 and 5 years were 95%, 73% and 73%, respectively. Time from diagnosis of metastases to SBRT was the only factor predictive of LC (HR 1.62, p  = 0.023). Median PFS was 8.6 months. Rates of OS at 1, 3 and 5 years were 88.5%, 56.6%, and 37.2%, respectively. Lesion greater than 30 mm (HR 1.82, p  = 0.030), presence of non-lung metastases (HR 1.67, p  = 0.020), the use of systemic treatment before SBRT (HR 1.82, p  = 0.023), and progression of treated metastases (HR 1.80, p  = 0.007), were all predictive of worse OS. Conclusions: Stereotactic body radiation therapy represents an effective approach in the management of oligometastatic CRC. Control of treated oligometastases seems to be a strong positive predictive factor for both PFS and OS.